Association between seroprevalence of measles and various social determinants in the year following a measles outbreak in Turkey. (June 2017) - Emek, M.; Islek, D.; Atasoylu, G.; Ozbek, O.A.; Ceylan, A.; Acikgoz, A.; Tay, Z.; Demiral, Y.; Oktem, M.A.; Unal, B.
Abstract: Objectives: Despite an ongoing measles elimination programme, a measles outbreak occurred in 2013 in Turkey. Population-based seroprevalence studies are needed to determine seronegativity and explore the reasons for this outbreak. This study aimed to explore the seroprevalence of measles and its association with various social determinants in a provincial population in Turkey in the year following a measles outbreak. Study design: Cross-sectional study. Methods: This study was conducted in Manisa Province in 2014 in a sample of 1740 people aged >2 years. The dependent variable was the seroprevalence of measles. Independent variables were sex, age, migration, household size, household density, income, education level, existence of chronic disease and occupational class. Blood samples were collected from participants at family health centres. The presence of specific measles antibodies in serum samples was determined using an anti-measles virus IgG enzyme-linked immunosorbent assay test. Chi-squared test and logistic regression analysis were performed. Results: Overall, data from 1250 people were analysed. The seroprevalence of measles in the whole study population was 82.2% (95% confidence interval 80.0–84.2). Seroprevalence was 55.4% among subjects aged 2–9 years, 48.7% among subjects aged 10–19 years, 74.1% among subjects aged 20–29 years and 93.6% among subjects aged 30–39 years ( P  < 0.01). Seroprevalence in subjects aged >40 years was >95%. The lowest seroprevalence was found in primary school children (40.2%), followed by those below the age for primary education (69.8%) and secondary school graduates (75.1%). The prevalence of measles seronegativity was not associated with any of the social determinants when adjusted for age. Conclusions: The seroprevalence of measles was lower than expected in the study population and was particularly low in subjects aged <30 years of age despite previous vaccination. Seroprevalence was not associated with social determinants of health that confirmed either an even distribution of virus exposure or fair access to vaccination services. However, the current seroprevalence cannot be sufficiently effective to reach the measles elimination targets, suggesting that it may be necessary to re-evaluate the need for an extra dose of measles vaccine. Highlights: Measles seroprevalence was lower than expected in a province population. Measles seroprevalence was low under 30 years of age despite previous vaccination. Measles seroprevalence was not associated with any social determinants of health. Current seroprevalence cannot be effective enough for measles elimination. The need for an extra dose of measles vaccine should be re-evaluated.